The Title and the Paragraph as Text Constituting Units - HOVHANNISYAN, SIRANUSH (Bulletin of Yerevan University B: Philology, 2021)
The text is a way of expressing and alienating the author’s thoughts. From this perspective thought is some kind of supercontent which is embedded in linguistic forms. As a complex structure, the text implies in its structure units of relatively small size. Paragraph appears to be such a unit. The paragraph is a carrier of a content node with the help of which text supercontent is completed for perceivers. Another text unit is the title which can be absent in some texts. If the text has a title it means the text is specifically-targeted one, that is, in this case, the author defines supercontent for perceivers. But if the text does not have a title, so it is free targeted text and to some extent, perceivers are free in the selection of supercontent. On content coverage title and paragraph are opposed to each other. The title, despite its relatively compact shape, has a broader content whereas the paragraph despite its broader shape has a relatively smaller content.